Lithium toxicity profile: A systematic review and meta-analysis - Adida, M; McKnight, R; Budge, K; Stockton, S; Goodwin, G; Geddes, J (2014)
Objectives: Lithium is a widely used and effective treatment for mood disorders. There has been concern about the safety of lithium but no adequate recent synthesis of the evidence on adverse effects was published in French language. The objective of this study was to produce a clinically informative, systematic toxicity profile of lithium. Materials and methods: We up-to-dated the systematic review and meta-analysis of randomized controlled trials and observational studies investigating the association between lithium and all reported major adverse effects that we previously published. We searched electronic databases specialist journals, reference lists, textbooks and conference abstracts. We used a hierarchy of evidence which considered RCTs, cohorts, case-control studies and case reports including patients with mood disorders treated with lithium. Outcome measures were renal, thyroid and parathyroid function; weight change, skin disorders, hair disorders and teratogenicity. Results: Five thousand nine hundred and eighty-eight abstracts were screened for eligibility and 390 studies included in the analysis. On average, glomerular filtration rate was reduced by -9.30 mls/min [95 % CI -12.15 to -6.44, P < 0.001] and urinary concentrating ability was reduced by 15 % of normal maximum. Lithium use may increase rates of renal failure but absolute risk appears to be of the order of 0.3 %. The prevalence of clinical hypothyroidism was increased in patients taking lithium [OR 5.78, 95 % CI 2.00 to 16.67, P = 0.001], whilst thyroid stimulating hormone was increased on average by 4.00 iU/mL [95 % CI 3.90 to 4.10, P = < 0.001]. Lithium treatment was associated with increased blood calcium [+0.09 mmol/L, 95 % CI 0.02 to 0.09; P = 0.009], and parathyroid hormone [+7.32 pg/mL, 95 % CI 3.42 to 11.23; P < 0.001]. Lithium was associated with more weight gain than placebo [OR 1.89 (1.27 to 2.82) P = 0.002], but not olanzapine [OR 0.32 (0.21 to 0.49) P ≤ 0.001]. There was no statistically significant increased risk of congenital malformations, alopecia, or skin disorders despite many suggesting such associations. Conclusions: Lithium is associated with increased risk of reduced urinary concentrating ability, hypothyroidism, hyperparathyroidism and weight gain. There is little evidence for a clinically significant reduction in renal function in the majority of patients and the risk of end-stage renal failure is low. The risk of congenital malformations is uncertain; the balance of risks should be considered before lithium is withdrawn during pregnancy. The consistent finding of a high prevalence of hyperparathyroidism means calcium levels should be checked before and during treatment. © 2014 Elsevier Masson SAS. All rights reserved.